INTRINSIC ANHARMONICITY IN EQUATIONS OF STATE OF SOLIDS AND MINERALS - Dorogokupets P.I.; Oganov A.R. (My University, 2004)
Two approaches in constructing equations of state accounting intrinsic anharmonicity are considered: D.C. Wallance's model, in which entropy is primary, and presently standard model, where primary is the Helmholtz free energy. It is shown that the final expressions for thermodynamic functions in these models are different. The differences in full thermodynamic functions can be as much as 1.5-2% in dependence on conditions. In spite of that, in the standard model all classic limits are satisfied, this enabling to use also the equations of state for analyzing PVT-relations for compounds and minerals.